The Benchmarking and Necessity of its Application in the System of Quality Management at the Enterprises of Pharmaceutical Industry - Zoidze Diana R. (Bìznes Inform, 2018)
The article is aimed at researching benchmarking and the need for its application in the management of pharmaceutical enterprises. As a result of generalizing the existing approaches the content of concept of «benchmarking» is defined. It is suggested to consider benchmarking as marketing tool, used by enterprise management. The stages of development of benchmarking are researched. The approach to benchmarking types and algorithm of its application in the enterprise is systematized and generalized. It is recommended to use benchmarking as a mandatory component of the quality management system to achieve sustainable success in pharmaceutical companies. The importance of benchmarking for business entities in the pharmaceutical market is clarified. The establishment and development of the quality system in the pharmaceutical industry of Ukraine are analyzed. The aim of further research in this direction should be solving the issues that prevent the effective use of benchmarking in enterprises. A special place among them is the need to spread the practice of benchmarking among the domestic top management.